2017
DOI: 10.1074/jbc.m116.767921
|View full text |Cite
|
Sign up to set email alerts
|

The RecJ2 protein in the thermophilic archaeon Thermoplasma acidophilum is a 3′-5′ exonuclease that associates with a DNA replication complex

Abstract: RecJ/cell division cycle 45 (Cdc45) proteins are widely conserved in the three domains of life, in bacteria, Eukarya, and Archaea. Bacterial RecJ is a 5'-3' exonuclease and functions in DNA repair pathways by using its 5'-3' exonuclease activity. Eukaryotic Cdc45 has no identified enzymatic activity but participates in the CMG complex, so named because it is composed of Cdc45, minichromosome maintenance protein complex (MCM) proteins 2-7, and GINS complex proteins (Sld5, Psf11-3). Eukaryotic Cdc45 and bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…We selected three other species, Thermoplasma acidophilum , Archeoglobus fulgidus , and Methanococcus voltae , to characterize the enzymatic activities of their RecJ homologs. For T. acidophilum we confirmed the 5′ exonuclease of RecJ1 and the 3′ exonuclease of RecJ2 [ 31 ]. The two RecJ1s from A. fulgidus and M. voltae were also 5′ exonuclease specific on ssDNA, while we could not identify any nuclease activity of their RecJ2s.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…We selected three other species, Thermoplasma acidophilum , Archeoglobus fulgidus , and Methanococcus voltae , to characterize the enzymatic activities of their RecJ homologs. For T. acidophilum we confirmed the 5′ exonuclease of RecJ1 and the 3′ exonuclease of RecJ2 [ 31 ]. The two RecJ1s from A. fulgidus and M. voltae were also 5′ exonuclease specific on ssDNA, while we could not identify any nuclease activity of their RecJ2s.…”
Section: Discussionmentioning
confidence: 77%
“…Surprisingly, both MjaRecJs did not form a complex with MjaGINS. However, the work on the RecJs from Thermoplasma acidophilum showed that TacRecJ2 forms a complex with GINS, but TacRecJ1 not [ 31 ]. Our result on MjaRecJ1 is consistent to that of TacRecJ1, but MjaRecJ2 showed the result contrary to TacRecJ2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T. acidophylum, a thermoacidophilic eukaryarcheon of the order Thermoplasmatales, encodes a pair of RecJ-like proteins, designated TaRecJ1 and TaRecJ2 (see Table 1), both of which are members of the RecJ clade that includes TkoGAN (23) E. coli was able to partially rescue the UV sensitivity of a recJ mutant strain, implying at least partial conservation of function across evolution (24).…”
mentioning
confidence: 99%